The automatic optimisation of drilling performance - Rowsell, Philip J. (1991)
The drilling industry, along with many others, is becoming increasingly competitive, demanding greater efforts to improve safety and reduce costs. For this reason, companies are progressively looking towards computerised automation to enhance performance. Unlike most industries however, the drilling industry has been slow to take advantage of the advances in computer and automation technology. Only recently have automatic operations such as tubular handling been placed under computer control. These activities relate to peripheral mechanical handling problems which are relatively easy to solve. The concept of an automatic intelligent drill, capable of making its own or assisted decisions about drilling parameters such as weight on bit or rotational speed, may seem remote and far into the future.